2009
DOI: 10.1016/j.ijsolstr.2008.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of piezoelectric laminated slightly curved beams using distributed transfer function method

Abstract: a b s t r a c tPiezoelectric laminated slightly curved beams (PLSCB) is currently one of the most popular actuators used in smart structure applications due to the fact that these actuators are small, lightweight, quick response and relatively high force output. This paper presents an analytical model of PLSCB, which includes the computation of natural frequencies, mode shapes and transfer function formulation using the distributed transfer function method (DTFM). By setting the radius of curvature of the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Proulx and Cheng [6] reported a dynamic model for the active vibration control of a rectangular plate using piezoceramic elements of arbitrary shape. Susanto [7] presented an analytical model of piezoelectric laminated slightly curved beams, which included the computation of natural frequencies, mode shapes and transfer function formulation using the distributed transfer function method. Qiu et al [8] used piezoelectric ceramic patches as sensors and actuators to suppress the vibration of a smart flexible clamped plate.…”
Section: Introductionmentioning
confidence: 99%
“…Proulx and Cheng [6] reported a dynamic model for the active vibration control of a rectangular plate using piezoceramic elements of arbitrary shape. Susanto [7] presented an analytical model of piezoelectric laminated slightly curved beams, which included the computation of natural frequencies, mode shapes and transfer function formulation using the distributed transfer function method. Qiu et al [8] used piezoelectric ceramic patches as sensors and actuators to suppress the vibration of a smart flexible clamped plate.…”
Section: Introductionmentioning
confidence: 99%
“…• Because of shallow curved beam assumption, the change in the radius of curvature due to magnetic field effects on the magnetostrictive layers is negligible [Susanto, 2009;Lee and Reddy, 2004].…”
Section: Analytical Solution For Free Vibration Of Laminated Curved Beammentioning
confidence: 99%
“…Also they proposed the global-local HSDT suitable for symmetric and anti-symmetric laminates. Susanto [2009] computation of natural frequencies, mode shapes and transfer function formulation using the distributed transfer function method (DTFM). The DTFM was applied and extended to carry out the transfer function formulation of the PLSCB and PLSB models.…”
Section: Introductionmentioning
confidence: 99%
“…The bending results were derived using Taylor series expansion method. Influence of stretching–bending coupling due to curvature on the electro-elastic behaviors of the piezoelectric laminated slightly curved beams was mentioned by Susanto [7]. The numerical results showed that increasing the radius of curvature leads to increase of the natural frequencies of curved beam.…”
Section: Introductionmentioning
confidence: 99%